How Crosscutting Is the Energy Concept within Physics Teaching and Learning - Eugenia Etkina; Jon Owen; Gorazd Planinsic; Lane Seeley (Education Sciences, 2023)
Much of the attention on the crosscutting concepts within the Next-Generation Science Standards (NGSSs) have gone to their coherence across different STEM disciplines. In this paper, we raise the question of the coherence of the energy concept within the teaching and learning of physics itself. Our investigations of teachers’ and students’ approach to solving problems, where both mechanical and thermal energy play equally important roles, indicate that the separation of energy studies in different units (mechanics, thermodynamics, etc.) leads to a cognitive disconnect of the understanding of different energy types and the inability to explain processes that involve both mechanical and internal energy, especially when the internal energy of the living organisms that are associated with a process is involved. We also find that when students gain experience analyzing scenarios where thermal energy plays a subtle yet critical role in addition to mechanical energy, they are able to apply this understanding to novel scenarios.